Effects of Pregnancy and Bacterial Vaginosis on Proinflammatory Cytokine and Secretory Leukocyte Protease Inhibitor Concentrations in Vaginal Secretions. (25th July 2010) - Balkus, Jennifer; Agnew, Kathy; Lawler, Richard; Mitchell, Caroline; Hitti, Jane
Abstract : We compared vaginal proinflammatory cytokine and secretory leukocyte protease inhibitor (SLPI) concentrations among pregnant and nonpregnant women according to bacterial vaginosis (BV) status. One-hundred and twenty-two women at 12–20 weeks' gestation and 133 nonpregnant controls had vaginal concentrations of interleukin (IL)-1 β, IL-6, IL-8, and SLPI measured by enzyme immunoassay. Multivariable linear regression was used to evaluate factors independently associated with vaginal cytokine and SLPI response. Pregnancy and BV were both independently associated with increased vaginal concentrations of IL-1 β and IL-8; pregnant women had increased concentrations of SLPI, while women with BV had decreased SLPI concentrations.